2007
DOI: 10.2174/156802607780636717
|View full text |Cite
|
Sign up to set email alerts
|

Dual Carbonic Anhydrase - Cyclooxygenase-2 Inhibitors

Abstract: Cyclooxygenase is a key enzyme responsible for metabolisation of arachidonic acid into prostaglandins and thromboxane. This enzyme is the target of non steroidal anti-inflammatory drugs (NSAIDs), used against inflammation and pain. The inducible COX-2 was associated with inflammatory conditions, whereas the constitutive form (COX-1) was responsible for the beneficial effects of the PGs. This observation led to the development of COX-2 inhibitors or "coxibs" of which rofecoxib (Vioxx) characterized by a methyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Part of the core structure of the oxicam class includes a S-N bond into a ring structure, dioxothiazine ring structurally resembling the sulfonamide bond. COX-2 inhibitors valdecoxib, celecoxib, and metamizole also inhibit CAII [41]. No studies have been done that evaluate the potential role for carbonic anhydrase II inhibition in the pathogenesis of SJS.…”
Section: Results: Disproportionate Molecular Targets Identified By Damentioning
confidence: 99%
“…Part of the core structure of the oxicam class includes a S-N bond into a ring structure, dioxothiazine ring structurally resembling the sulfonamide bond. COX-2 inhibitors valdecoxib, celecoxib, and metamizole also inhibit CAII [41]. No studies have been done that evaluate the potential role for carbonic anhydrase II inhibition in the pathogenesis of SJS.…”
Section: Results: Disproportionate Molecular Targets Identified By Damentioning
confidence: 99%
“…Different classes of sulfonamides and related compounds can efficiently inhibit CA IX in vitro and some of them showed anticancer effect also in vivo in xenografted subcutaneous or metastatic animal models [77,84]. Interestingly, CA IX activity can be inhibited also by celecoxib and valdecoxib, sulfonamide inhibitors of cyclooxygense 2 (COX-2), which is a key enzyme of arachidonic acid metabolism involved in colorectal carcinoma [147,148]. This may suggest that the mode of action of these COX-2 inhibitors could involve targeting of CAs.…”
Section: Ca IX As a Therapy Targetmentioning
confidence: 99%
“…Indeed, Macias and coauthors have shown that celecoxib can prolong action potential duration in mouse cardiac myocytes while shortening it in guinea pig cardiac myocytes [13]. An additional layer of complexity to this picture is added by possible interaction of coxibs with other molecular targets that could alter cell functioning but are not related to ion channels, such as the coxibs' main receptor, COX-2, or carbonic anhydrases [1], [7]. Thus, although apparently no single ‘ideal’ model organism for studying ion channel-related effects of coxibs exists, the well-studied Drosophila , which conveniently lacks cyclooxygenases, provides a good experimental setting for basic research in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the drug inhibits carbonic anhydrases with nanomolar affinity [1], while at low micromolar concentrations it alters functioning of voltage-activated Na + , K + and Ca 2+ channels [2], [3], [4], [5], induces cytotoxicity towards cardiomyocytes [6], triggers apoptosis and blocks cell cycle progression [1], [7].…”
Section: Introductionmentioning
confidence: 99%